2009
DOI: 10.1080/03630240903158420
|View full text |Cite
|
Sign up to set email alerts
|

Singaporean Women's Knowledge of Human Papillomavirus (HPV) and Attitudes Toward HPV Vaccination

Abstract: With a vaccination program currently planned to protect Singaporean women from human papillomavirus, a need arises for assessing Singaporean women's knowledge of human papillomavirus and attitudes toward human papillomavirus vaccination to identify barriers to a successful program and to help inform health education campaigns. A representative sample of 2,145 women aged between 18 and 49 years were randomly selected from households throughout Singapore and interviewed with a similar questionnaire to that used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
0
29
1
Order By: Relevance
“…This may related to HPV vaccine marketing in Korea. Similar to the marketing in other Asian countries (Hsu et al, 2009;Pitts et al, 2009), the HPV vaccine in Korea has been marketed as an anticancer vaccine and not a vaccine against an STD caused by HPV infection (Kang & Kim, 2011). Therefore, female college students in Korea have not perceived benefits of the HPV vaccine to prevent genital warts and HPV and do not considered themselves targets for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…This may related to HPV vaccine marketing in Korea. Similar to the marketing in other Asian countries (Hsu et al, 2009;Pitts et al, 2009), the HPV vaccine in Korea has been marketed as an anticancer vaccine and not a vaccine against an STD caused by HPV infection (Kang & Kim, 2011). Therefore, female college students in Korea have not perceived benefits of the HPV vaccine to prevent genital warts and HPV and do not considered themselves targets for HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies report that HCW are the most trusted, preferred and influential source of HPV vaccine information for adolescents and parents. [20][21][22] There were mixed results reported regarding HCW recommendation of HPV vaccines -despite its importance. A study reported a 93-fold increase of HPV vaccination uptake because of HCW discussion and recommendation of HPV vaccination.…”
mentioning
confidence: 98%
“…The TPB model predicts that women have higher intentions to utilize cervical cancer prevention measures if they hold favorable attitudes (Jennings-Dozier, 1999;Linton, 2009;Teitelman et al, 2011). Studies have reported significant associations between cervical cancer prevention measures and attitudinal relatedfactors such as pain, embarrassment, and fear (Pitts et al, 2009;Steven et al, 2004), inconvenience and cost (Kuitto et al, 2010;Tan, 2013), and health benefits (Reid, 2001).…”
Section: Research-article2014mentioning
confidence: 99%
“…Injunctive norm is the approval or disapproval of vaccination or Pap smear by important social referent figures. For example, in South-East Asian countries, parents and doctors may express negative concerns about sexual promiscuity and side effects (Chow et al, 2010;Pitts et al, 2009). Women also seek the approval of their relationship partner (Yeoh et al, 2006).…”
Section: Research-article2014mentioning
confidence: 99%
See 1 more Smart Citation